MULTIMODALITY IN THE “THINK GLOBALLY ACT LOCALLY” ENGLISH TEXTBOOK - Annisa Fadhilah Harahap; Indra Hartoyo (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
The objectives of this study were: (1) to identify the components of multimodality that are applied in the textbook entitled "Think Globally Act Locally" (2) to describe how the components of multimodality create meaning. This study used descriptive qualitative design. The data in this study are in the form of verbal mode (caption text and instruction text) and image and visual mode (the illustration and the arrangement). The data were collected by analyzing the textbook directly and written down in a notebook. The findings of this study revealed that: (1) there were three components of multimodality in the textbook, namely verbal, image, and visual mode. (2) Each component that appears has a different type but has its own role in creating the same meaning. These components appear simultaneously so that they are in sync with each other. This study found that 76% of the verbal mode is a statement and 24% of the verbal mode is a command. Thus, Statement is the dominant Speech Function. This study also found that the dominant representation is narrative representation with human participants. The dominant interactions in this study are offer in gaze, close shot in size of frame, frontal angle in horizontal angle, and high level in vertical angle. And the dominant compositions in this study are top, center, bottom, and right in information value, placement, color, and sharpness in salience, and framed in framing.